INFORMATIKA PÁNINEN ELEKTRON OQÍW QOLLANBALARDÍ JARATÍWǴA QOYÍLATUǴÍN TALAPLAR HÁM JARATÍW BASQÍSHLARÍ - Kazbekova, E. (SCIENCE and SOCIETY, 2024)
This article discusses the requirements and criteria for creating e-learning manuals. The article focuses mainly on digitization of education and the need to use electronic textbooks in education.